Structural characterization of a variety of spider silks from Turkey using different biophysical techniques. Issue 3 (2011) - İde, Semra and Bayarı, Sevgi Haman and Türkeş, Tuncay and Mergen, Y. Orhan and Çelik, Ömer and Bütün, Vural and Sargon, Mustafa F. and Kocatepe, Neslihan and Kriechbaum, Manfred
Abstract : Various experimental methods (XRD, FTIR, SAXS, DLS and SEM) were used to investigate structures of the silk samples weaved by spiders in Turkey. Silk samples were collected from the natural habitats belonging to the spider species (i.e., Near Salt Lake/şereflikoçhisar, İvriz Dam/Ereǧli-Konya, Karataş Lake/Burdur and several locations in Black Sea Region of Turkey). Among all collected species, Araneidae (Araneus angulatus, Argiope bruennichi, Argiope lobata, Larinoides cornutus), Eresidae (Eresus cinnaberinus), Agelenidae (Agelena labyrinthica), Oecobidae (Uroctea durandi), Miturgidae (Cheiracanthium erraticum), Salticidae (Heliophanus flavipes, Philaeus chrysops), Theridiidae (Steatoda paykulliana) and Gnaphosidae were found significant amongst other spider species. Structural differences and similarities of these species were reported. Diameter range of draglines, inter crystallite distance of nano-size structures, mean size range of nano-structure aggregations, crystallite size range, information about protein content were obtained. The mechanical properties of some silk fibers were also investigated.